Wars and Peasants in North Šäwa, Ethiopia (1855–1916) - Abebe, Dechasa (Aethiopica, 2017)
Conflicts and wars are associated with Ethiopian monarchs throughout history. It might be assumed that the presence of a monarch in a certain province within the country would assure peace and security. However, the opposite appears to be true for much of the history of Ethiopia. North Šäwa experienced a number of wars, conflicts, and predatory raids when its autonomy and relative peace was disrupted by its subjugation to Emperor Tewodros II in 1855. This was followed by Šäwan resistance, a time labelled as a ‘period of anarchy’ by Šäwan authors. The return of Mǝnilǝk from Mäqdäla to Šäwa in 1865 also caused confrontations among power contenders of Šäwa. The transitional period between the reigns of Emperor Mǝnilǝk and Emperor Ḫaylä Śǝllase was also characterized by similar uncertainties which reached their climax in 1916. In a time of relative peace, the autumn of 1895, Šäwan peasants were forced to feed thousands of soldiers from the southern regions of the country on their way to ʿAdwa. The Battle of Sägäle in October 1916 fought on Šäwan soil had a catastrophic impact on the life of local peasantry that forced the government to promise compensation and rehabilitation, a rare practice at that time. Moreover the region was affected by different forms of intermittent conflicts on religious and ethnic pretexts. Interand intraethnic conflicts arose for both economic and cultural reasons. The article attempts to analyse the impacts of the recurrent wars on the life of north Šäwan peasants from 1855 to 1916.